2009
DOI: 10.1007/s00280-009-0976-y
|View full text |Cite
|
Sign up to set email alerts
|

Do anthocyanins and anthocyanidins, cancer chemopreventive pigments in the diet, merit development as potential drugs?

Abstract: Anthocyanins, plant pigments in fruits and berries, have been shown to delay cancer development in rodent models of carcinogenesis, especially those of the colorectal tract. Anthocyanins and anthocyanidins, their aglycons, especially cyanidin and delphinidin, have been subjected to extensive mechanistic studies. In cells in vitro, both glycosides and aglycons engage an array of anti-oncogenic mechanisms including anti-proliferation, induction of apoptosis and inhibition of activities of oncogenic transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 74 publications
(8 reference statements)
2
66
0
Order By: Relevance
“…Cancer The preventive and suppressive effects of anthocyanins on cancer have been demonstrated in many studies, and key findings in this area can be found in the literature (Thomasset et al, 2009;Prasad et al, 2010). In general, anthocyanins suppress inflammatory pathways associated with cancer pathogenesis.…”
Section: Other Health Benefits Of Anthocyanins: Anthocyanins In Relatmentioning
confidence: 99%
“…Cancer The preventive and suppressive effects of anthocyanins on cancer have been demonstrated in many studies, and key findings in this area can be found in the literature (Thomasset et al, 2009;Prasad et al, 2010). In general, anthocyanins suppress inflammatory pathways associated with cancer pathogenesis.…”
Section: Other Health Benefits Of Anthocyanins: Anthocyanins In Relatmentioning
confidence: 99%
“…They are generally found in nature as glycosides, called anthocyanins, and are responsible for the blue, red, or purple colors of plants. Anthocyanin-rich extracts demonstrated chemopreventive activities against cancer in animal models of carcinogenesis [50]. Single agents have been tested in in vitro models and have shown interesting anti-proliferative and proapoptotic properties, acting by modulating survival pathways such as NFjB [51] or MAPK [52].…”
Section: Anthocyanidinsmentioning
confidence: 99%
“…Some studies specify the anticarcinogenic effect of anthocyanins [12,13,19,111,112,[133][134][135]. They inhibit the growth of carcinogenic cells that provoke colon cancer, induce the apoptosis effect, have the capacity to inhibit in vitro the growth of cells that cause tumours in humans and are even able to act as modulators of the macrophages in the immune response [89,112].…”
Section: Flavonoids -From Biosynthesis To Human Health 212mentioning
confidence: 99%